2003
DOI: 10.1063/1.1540130
|View full text |Cite
|
Sign up to set email alerts
|

Extraordinary magnetoelasticity and lattice softening in bcc Fe-Ga alloys

Abstract: Extraordinary magnetostrictive behavior has been observed in Fe-Ga alloys with concentrations of Ga between 4% and 27%. λ 100 exhibits two peaks as a function of Ga content. At room temperature, λ 100 reaches a maximum of 265 ppm near 19% Ga and 235 ppm near 27% Ga. For compositions between 19% and 27%, λ 100 drops sharply to a minimum near 24% Ga and exhibits an anomalous temperature dependence, decreasing by as much as a factor of 2 at low temperatures. This unusual magnetostrictive behavior is interpreted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
329
0
17

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 535 publications
(364 citation statements)
references
References 9 publications
18
329
0
17
Order By: Relevance
“…[1][2][3][4][5] Particularly, high values of magnetostriction ͑400 ppm͒ are observed along the ͗100͘ direction for x = 0.19 and 0.28, and within this concentration range the magnetostriction has a minimum of about 250 ppm at x = 0.225, 6 which is still a very high value compared to the 20 ppm of pure iron. A detailed structural investigation of the phase relations in single crystals show a strong dependence of the magnetostriction on the Ga concentration and on the sample thermal history as well as on the state of the chemical ordering in these alloys.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…[1][2][3][4][5] Particularly, high values of magnetostriction ͑400 ppm͒ are observed along the ͗100͘ direction for x = 0.19 and 0.28, and within this concentration range the magnetostriction has a minimum of about 250 ppm at x = 0.225, 6 which is still a very high value compared to the 20 ppm of pure iron. A detailed structural investigation of the phase relations in single crystals show a strong dependence of the magnetostriction on the Ga concentration and on the sample thermal history as well as on the state of the chemical ordering in these alloys.…”
Section: Introductionmentioning
confidence: 78%
“…A detailed structural investigation of the phase relations in single crystals show a strong dependence of the magnetostriction on the Ga concentration and on the sample thermal history as well as on the state of the chemical ordering in these alloys. 6 In slow cooled samples for 0.225 Ͻ x Ͻ 0.28 only the DO 3 phase is present and the magnetostriction increases monotonically with x; in quenched alloys for x = 0.25 is observed a phase mixture of A2, B2, and DO 3 phases and the magnetostriction is enhanced as compared to the slow cooled samples ͑with single phase DO 3 ͒. The mixture of A2 and DO 3 phases is most stable in the metastable bcc region of the Fe-Ga phase diagram where the maximum magnetostriction is detected.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of Fe 1Àx Ga x alloys cooled (postgrowth) at 10 C= min have shown the presence of two anomalous peaks in the magnetostriction. The first peak at x % 0:19 has been attributed to an increase in the magnetoelastic coupling, resulting from the formation of short-range ordered (SRO) Ga pairs along the [100] axis of the A2 structure [5], and the second at x % 0:27 to a softening of the shear modulus c 0 ¼ ðc 11 -c 12 Þ=2 [6,7]. Of special note is the fact that both 3 100 =2 and the presence of a two-phase region (A2 þ DO 3 ) depend sensitively on thermal history; this suggests that the enhanced magnetostriction is due to an underlying heterogeneity rather than a conventional homogeneous ferromagnetic phase.…”
mentioning
confidence: 99%
“…Recently, a number of investigations have focused on Fe-Ga ͑Galfenol͒ alloys due to the combination of its high mechanical strength, good ductility, relatively large ͑3/2͒ 100 values, low saturation fields, high blocking stress, and low cost. [2][3][4][5][6][7] Galfenol has potential applications in acoustic projectors, acoustic sensors, and actuators. 8,9 Magnetoelectric materials have been very interesting since early Swiss 10 and Russian 11 work, and have recently had a renaissance ͑now commonly called multiferroic͒ in Nature, Science, Phys.…”
Section: Introductionmentioning
confidence: 99%